Assessment of the authenticity of a semiempirical turbulent combustion method in afterburner of a gas turbine engine - Loginov, Vasyl; Rublov, Volodymyr; Yelansky, Аlexandr (Technology audit and production reserves, 2020)
The object of research is the working process of the afterburner of the combustion chamber of a turbojet dual-circuit engine with flow mixing. The research was aimed at developing a comprehensive methodology for calculating the afterburner-output device of a forced turbojet engine, taking into account the unevenness of the coefficient of oxygen excess and flow turbulence. To calculate the process of mixture formation, let’s use the model of the separate flow of the gas and liquid phases, taking into account the influence of finite transfer rates between the phases. The gas phase is calculated using a numerical method based on the Eulerian-Lagrangian approach, which allows one to calculate a three-dimensional compressible unsteady flow in an afterburner and is described by Navier-Stokes equations with Reynolds averaging and a one-parameter model of turbulent viscosity. The differential equations of the liquid phase are solved by the Runge-Kutta method. Accounting for turbulent combustion is carried out using the semi-empirical theory. The main indicator of the afterburner combustion chamber working process is the coefficient of completeness of combustion, on which the engine thrust during forced operation depends. To evaluate the combustion efficiency, the fields of velocity, temperature, pressure, mass fraction of oxygen, fuel vapor and pulsation velocity are calculated. These values are determined by numerical simulation of a two-phase flow. The work uses a model of the separate flow of the gas and liquid phases, taking into account the influence of finite transfer rates between the phases. Having data of numerical calculation and a semi-empirical model, let’s determine the completeness of fuel combustion, depending on the coefficient of excess air and the length of the combustion zone. The technique used in this work allows to calculate the completeness of fuel combustion in the afterburner, and the calculation results coincide with experimental data with an error of no more than 7%. Having data on the completeness of combustion, one can determine the thrust of the nozzle during forced operation of the engine.